On an abstract nonlinear second order integrodifferential equation - M. B. Dhakne; G. B. Lamb (Journal of Function Spaces and Applications, 2007)
The aim of the present paper is to study the global existence of solutions of nonlinear second order integrodifferential equation in Banach space. Our analysis is based on an application of the Leray-Schauder alternative and rely on a priori bounds of solutions.